Courting the 'rich and restless': globalisation of real estate and the new spatial fixities of the super-rich in Singapore. Issue 1 (2nd January 2017) - Pow, C.P.
Abstract : How have the globalisation of real estate and the rise of a transnational class of super-rich homebuyers challenged conventional analyses of local residential property markets? What analytical tools and concepts can we deploy to understand the dialectical tensions between the local and global; fixity and motion as well as the deterritorialisation and reterritorialisation of real estate by the super-rich? Drawing on Singapore as a case study, this paper interrogates the new 'spatial fixities' of the super-rich housing market at two inter-related scales of analysis. At the national scale, this spatial fixity could be interpreted in terms of the attempts by the Singapore 'property state' to attract high net-worth individuals to reside and invest in the country as a 'quick fix' way to boost national capital. At the global scale, this new spatial fixity of highly mobile super-rich can be seen in their territorialisation strategies to constantly seek out new safe havens to physically 'park' and grow their wealth beyond the traditional confines of national boundaries. Insofar as these two kinds of spatial fixes both complement and feed off one another via conspicuous real estate development, they also risk colliding and generating social contradictions that may potentially threaten their symbiotic relations.